2018
DOI: 10.1002/lary.27595
|View full text |Cite
|
Sign up to set email alerts
|

Impact of high‐ versus low‐risk genotype on sinonasal radiographic disease in cystic fibrosis

Abstract: Objective Understanding of how specific mutations impact the cystic fibrosis transmembrane conductance regulator (CFTR) protein has given rise to the classification of CF patients into low‐risk and high‐risk genotypes. Few prior studies have investigated differences in sinonasal disease between low‐risk and high‐risk CF genotypes. This multi‐institutional review aimed to evaluate radiographic sinus disease severity based on genotype. Methods A review was conducted on adult patients with CF evaluated between 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 16 publications
2
13
0
Order By: Relevance
“…Proposed predictive criteria for ESS are: massive polyposis, prior history of ESS, high Lund-Mackay score, high SNOT-22 score and severe CFTR mutations [3,4]; delay in surgery did not affect post-operative improvement [5]. A preoperative evaluation of CT findings is essential to avoid complications; an intra-operative image guidance can be useful due to anatomic differences in CF patients, especially in revision cases [6]. ESS procedure in pediatric patients is totally safe [7].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Proposed predictive criteria for ESS are: massive polyposis, prior history of ESS, high Lund-Mackay score, high SNOT-22 score and severe CFTR mutations [3,4]; delay in surgery did not affect post-operative improvement [5]. A preoperative evaluation of CT findings is essential to avoid complications; an intra-operative image guidance can be useful due to anatomic differences in CF patients, especially in revision cases [6]. ESS procedure in pediatric patients is totally safe [7].…”
Section: Resultsmentioning
confidence: 99%
“…Informed consent was obtained from all patients for data publication. 6 National Heart and Lung Institute, Imperial College London, London, United Kingdom 7 Lungenheilkunde München-Pasing, Munich, Germany; 8 Centro Hospitalar Universitário Lisboa Norte, Lisbon, Portugal; 9 Assistance Publique-Hôpitaux de Paris, Adult Cystic Fibrosis Center, Cochin Hospital, Paris, France and Sorbonne Paris Cité, Université Paris Descartes, Paris, France; 10 Vertex Pharmaceuticals Incorporated, Boston, MA, USA Correspondence: Carlo Castellani (carlocastellani@gaslini.org) Italian Journal of Pediatrics 2020, 46(Suppl 1):A3…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sinus hypoplasia is so characteristic of this disease that it has been noted that CF diagnosis should be checked if the sphenoid's pneumatisation is apparently of normal size (105). Interestingly, there is a genotype-phenotype correlation for the sphenoid pneumatisation in CF (106,107). By far the most common mutation in the gene responsible for CF (108) is associated with a significantly lower sphenoid pneumatisation on lateral X-ray images of the skull compared to other pathogenic mutations in CF (106).…”
Section: Discussionmentioning
confidence: 99%
“…Complete ESS is especially important in CF CRS, as inspissated secretions may be trapped in partially removed partitions. A recent study also demonstrated high-risk CF mutations are associated with more severe radiographic findings as measured by modified Lund–Mackay scores, as well as higher prevalence of sinus hypoplasia/aplasia [18]. An understanding of CF pathophysiology is important in the surgical management of CF CRS patients to ensure surgical success.…”
Section: Surgical Managementmentioning
confidence: 99%